A problem with questions: Improvisation and unforeseen epistemology in animation practice. Issue 1 (1st August 2020) - Buchanan, Andrew
The typical research project ostensibly begins with a question. The notion of establishing 'questions worth answering' which can be satisfied with confirmable answers is an orientation originally adopted from the sciences, and highlights the practical imposition of the academy to create rigor and consistency. Brad Haseman has suggested that an alternative to the posing of questions for those pursuing practice-based research in the creative arts is to begin with an 'enthusiasm of practice' from which useful knowledge may be generated, but returns to the need for the researcher to ultimately articulate a problem (if not a question) to pass the research credibility test. Is the illocutionary act of this retrospective 'probleming' not the same as a question? As the question demands an answer, the problem demands a solution. Perhaps this is the defining edge between practice as research and, simply, practice. The alignment of problem and solution (or question and answer) is suspiciously neat, and the form of language demands that they match neatly. Leaning on the experience of my own practice-based Ph.D. in creative media, this article will describe the positioning of improvisational animation production as a mode of practice-enthusiasm that can serve both as methodology and as epistemology for knowledge production in animation research (and related practices). I will discuss potential research questions related to improvisation for animator-researchers, and suggest that this mode of practice can yield useful, verifiable knowledge without recourse to the question‐answer or the problem‐solution formulation. In fact, the imposition of these, even post hoc, may undermine the research value of improvised practice and its epistemological clarity. The enthusiasm in this case may be the lack of answers or solutions that (at least linguistically) terminate the very origin of the enthusiasm for the practice.